Decoding m6A readers: roles of YTHDF proteins in leukemogenesis and cancer immunity - Li, Chunhong; Chen, Xi; Pu, Shanrui; Lian, Kun; Li, Lihua; Jiang, Xiulin; Wang, Qiang (Frontiers in Immunology, 2025)
N6-methyladenosine (m6A) is the most prevalent internal modification in eukaryotic mRNA and plays critical roles in post-transcriptional gene regulation. Among the m6A regulators, YTH domain family proteins (YTHDF1, YTHDF2, and YTHDF3) act as major “readers” that interpret m6A marks and dictate the fate of modified transcripts through coordinated control of mRNA translation, stability, and decay. Recent advances have uncovered multifaceted roles of YTHDF proteins in both physiological hematopoiesis and pathological leukemogenesis. YTHDF2 is essential for hematopoietic stem cell (HSC) self-renewal and lineage commitment by selectively degrading transcripts that constrain stemness, while dysregulated YTHDF activity contributes to leukemic stem cell maintenance, metabolic adaptation, and therapy resistance. In parallel, YTHDF1 and YTHDF3 have been implicated in shaping the leukemic transcriptome and cooperating with oncogenic signaling pathways to promote malignant transformation. Beyond intrinsic leukemic functions, accumulating evidence highlights the impact of YTHDF proteins on tumor immunity. By modulating dendritic cell antigen presentation, T cell activation, and immune checkpoint expression, YTHDF proteins orchestrate the tumor immune microenvironment and influence anti-tumor immunity. These discoveries not only provide mechanistic insight into how m6A readers govern hematopoietic and immune regulation, but also open new therapeutic avenues. Pharmacological manipulation of YTHDF activity holds promise to selectively eradicate leukemic stem cells, enhance immune surveillance, and improve responses to conventional and immune-based therapies. In this review, we summarize the latest progress in understanding the functional roles and molecular mechanisms of YTHDF proteins in normal hematopoiesis, leukemogenesis, and cancer immunity, and discuss emerging strategies for targeting m6A readers in hematologic malignancies and immunotherapy.